Strategi Branding Dengan Menggunakan Instagram Pada Umkm Di Desa Brabowan, Sambong, Blora - Muzzazinah Muzzazinah; Ignatius Parlindungan; Tiffani Ayuning Tias; Fatimah Tuszahro; Gabriela Wina Pramesti; Rani Dwi Purwanti; Aldi Fahli Muzaqih; Firjatullah Kukuh Amirul Haq; Laurencia Dian Flaviana Agatha (Universitas Sebelas Maret, 2025)
Technological advancements are driving the business world to become more competitive with the presence of online promotions. This situation has pushed Micro, Small, and Medium Enterprises (MSMEs) to find something that sets them apart from other businesses, that is through branding strategies. Based on survey and observation, MSMEs in Brabowan Village, Sambong, Blora have low knowledge about business branding and its application with digital technology such as social media. Therefore, a socialization and assistance program was held for the Jula Juli and Suyitno Jewelry Box SMEs regarding the importance of branding for the development of their businesses. This activity is carried out in three stages: the initial stage, the implementation stage, and the final stage. The result of this activity is an Instagram account for each MSME that contains all the branding components such as brand identity including name, logo, slogan, color identity, and profile video.